The Existence and Integration of Customary Law, Positive Law, and Islamic Law in the Midst of Political Dynamics - Yasir, M; Mangar, Irma; Dewi, Taniya Shinta (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
This research aims to analyze the existence and integration of customary law, positive law, and Islamic law in facing contemporary global political dynamics. The research method used is normative legal research with a qualitative approach through literature studies. The results of the study show that the three legal systems continue to have a strategic role in Indonesia's national legal system despite facing the challenges of globalization, modernization, and the influence of universal values such as democracy and human rights. Customary law survives through cultural legitimacy and local wisdom, positive law through formal state authority, while Islamic law through religious legitimacy and its institutionalization in the national legal system. The study also found that the integration of the three legal systems is necessary to create a harmonious, adaptive, and equitable legal system. Such integration is not unification, but harmonization that allows each legal system to complement each other. The form of integration can be seen in the recognition of customary law, the application of Islamic law in certain fields, and the function of positive law as a link between local values and global norms. However, such integration faces challenges in the form of differences in principles, potential normative conflicts, and pressure on international legal standards. The novelty of this research lies in its integrative analysis based on legal pluralism in the context of contemporary global political dynamics.